Childhood abuse and reduced cortical thickness in brain regions involved in emotional processing. (20th September 2016) - Gold, Andrea L.; Sheridan, Margaret A.; Peverill, Matthew; Busso, Daniel S.; Lambert, Hilary K.; Alves, Sonia; Pine, Daniel S.; McLaughlin, Katie A.
Abstract : Background: Alterations in gray matter development represent a potential pathway through which childhood abuse is associated with psychopathology. Several prior studies find reduced volume and thickness of prefrontal (PFC) and temporal cortex regions in abused compared with nonabused adolescents, although most prior research is based on adults and volume‐based measures. This study tests the hypothesis that child abuse, independent of parental education, predicts reduced cortical thickness in prefrontal and temporal cortices as well as reduced gray mater volume (GMV) in subcortical regions during adolescence. Methods: Structural MRI scans were obtained from 21 adolescents exposed to physical and/or sexual abuse and 37 nonabused adolescents (ages 13–20). Abuse was operationalized using dichotomous and continuous measures. We examined associations between abuse and brain structure in several a priori‐defined regions, controlling for parental education, age, sex, race, and total brain volume for subcortical GMV. Significance was evaluated at p < .05 with a false discovery rate correction. Results: Child abuse exposure and severity were associated with reduced thickness in ventromedial prefrontal cortex (PFC), right lateral orbitofrontal cortex, right inferior frontal gyrus, bilateral parahippocampal gyrus (PHG), left temporal pole, and bilateral inferior, right middle, and right superior temporal gyri. Neither abuse measure predicted cortical surface area or subcortical GMV. Bilateral PHG thickness was inversely related to externalizing symptoms. Conclusions: Child abuse, an experience characterized by a high degree of threat, is associated with reduced cortical thickness in ventromedial and ventrolateral PFC and medial and lateral temporal cortex in adolescence. Reduced PHG thickness may be a mediator linking abuse with externalizing psychopathology, although prospective research is needed to evaluate this possibility.